1998
DOI: 10.1093/ije/27.2.199
|View full text |Cite
|
Sign up to set email alerts
|

The stability of lifestyle behaviour

Abstract: The four lifestyle behaviours differed in the degree of variation over a 4-year period. Only a small group (11%) changed two or more lifestyle behaviours. This implies that lifestyle behaviour is not a unified concept and should not be treated in that way in public health campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 14 publications
6
62
0
2
Order By: Relevance
“…While some studies have investigated dietary stability, many of these use dietary scores based on a limited number of foods or food behaviours and results between studies are inconsistent. Mulder et al (46) used a dietary score based on seven food behaviours and found great variability over a 4-year period, while Mishra et al (47) used a dietary pattern score based on factor analysis and found that healthier eating behaviours were more stable than other behaviours. In contrast, van Dam et al (48) found higher stability with the Western pattern in comparison to the 'Prudent' dietary pattern.…”
Section: Study Implicationsmentioning
confidence: 99%
“…While some studies have investigated dietary stability, many of these use dietary scores based on a limited number of foods or food behaviours and results between studies are inconsistent. Mulder et al (46) used a dietary score based on seven food behaviours and found great variability over a 4-year period, while Mishra et al (47) used a dietary pattern score based on factor analysis and found that healthier eating behaviours were more stable than other behaviours. In contrast, van Dam et al (48) found higher stability with the Western pattern in comparison to the 'Prudent' dietary pattern.…”
Section: Study Implicationsmentioning
confidence: 99%
“…In fact, dietary habits from a decade ago and those close to the presentation of the disease could both be of importance. Dietary habits are, however, relatively stable 2 and the ability to change food habits varies between individuals 3 . Dietary changes over time may occur because active decisions are made about lifestyle and dietary behaviours 4 -6 .…”
mentioning
confidence: 99%
“…En primer lugar, aquellas que son propias del diseño del estudio como es, por ejemplo, cierto grado de infradeclaración en determinadas variables recogidas en la encuesta 14 , o errores derivados de la conexión de los registros 15 . Respecto al análisis estadístico hay que tener en cuenta que no consideramos los cambios que se pueden producir en algunas variables a lo largo del tiempo 16 .…”
Section: Discussionunclassified